Insights on the effects of patient perceptions and awareness on ambulance usage in Karachi, Pakistan. Issue 12 (10th September 2013) - Chandran, Aruna; Ejaz, Kiran; Karani, Rabia; Baqir, Muhammad; Razzak, Junaid; Hyder, Adnan A
Abstract : Background: Prehospital care is a vital part of emergency medical care. Countries with decentralised ambulance systems, such as Pakistan, require patient knowledge as to when to call an ambulance and which service to call. Little is known about how patient perceptions of ambulance services affect ambulance usage in most low- and middle-income countries (LMIC). The purpose of our study was to analyse patient perspectives of the ambulance system in Karachi to understand how to improve ambulance use. Methods: Indepth interviews were conducted with 30 individuals selected by convenience sampling representing patients who came to the emergency department by private transport versus one of two of the main ambulance service providers in Karachi. Results: Similar to what has been shown in some LMIC contexts, two of the major themes that emerged which affect patient decision making with regard to ambulance use were a mistrust of the ambulance system or providers and a sense of inadequacy of the local system as compared with international standards. In addition, which has not been shown in previous studies, there was a fundamental misunderstanding of the role of ambulance services in the healthcare infrastructure. Conclusions: Insight into the main issues affecting patient decisions to use an ambulance service offers possible targets for patient education that could result in an increase in the proper usage of ambulances and thus optimise outcomes from serious injury and illness in an LMIC context.